Resilience, Parenting Style, and Children's Eating Behavior. (June 2019) - Wood, Matthew; Shukla, Paurav
This study aims to gain a deeper understanding of the relationship between parental resilience and parenting styles and the impact of these characteristics on children's eating behaviors and weight. Through a quantitative examination, we found parental concerns about their child's weight positively relate to family attitudes toward fruits and vegetables but negatively relate to actual consumption of fruits and vegetables. Contrarily, advance planning of healthy meals among parents is negatively associated with family attitudes toward fruits and vegetables but positively associated with children's consumption of fruits and vegetables. Family attitudes toward fruits and vegetables have a significant influence on children's consumption of fruits and vegetables. The personal competence component of parental resilience has a significant moderating influence on the relationship between parental concerns about their child's weight and his or her consumption of fruits and vegetables. The "acceptance of self and life" component of parental resilience has a significant moderating influence on the relationship between advance planning of healthy meals among parents and children's consumption of fruits and vegetables.